Pengaruh Motivasi Kerja, Mutasi, dan Pelatihan terhadap Prestasi Kerja ASN: Peran Mediasi Kepuasan Kerja pada Pangkalan Sarana Operasi Bea dan Cukai Tipe B Sorong - Muhammad Ashari Natsir; Amir Tengku Ramly; Zainur Hidayah (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
This study examines the effects of work motivation, job transfer, and training on the job performance of Indonesian civil servants (ASN) at the Customs and Excise Operational Facilities Base, Type B Sorong, with job satisfaction as a mediating variable. A quantitative explanatory design was applied using a census approach involving all active ASN employees (n = 77). Data were collected through a structured questionnaire and analyzed using PLS-SEM with SmartPLS. The results show that work motivation, job transfer, and training have positive and significant effects on job satisfaction, while job satisfaction positively and significantly affects job performance. Moreover, all three predictors also have direct positive and significant effects on job performance, with training identified as the strongest predictor. Indirect-effect testing confirms that job satisfaction significantly mediates the relationships between motivation, job transfer, and training and job performance, indicating complementary partial mediation. Practically, the findings underscore the importance of competency-based job transfers, relevant training that supports transfer to operational duties, and strategies to enhance motivation to strengthen both job satisfaction and performance.